Pierre Duviols: La destrucción de las religiones andinas (durante la Conquista y la Colonia) - Klor de Alva, Jorge (Pontificia Universidad Católica del Perú. Fondo Editorial, 1988)
Does not contain a summary.
Pierre Duviols: The destruction of the Andean religions (during the Conquest and the Colony)
Keywords: Antropología; https://purl.org/pe-repo/ocde/ford#5.04.03